2016
DOI: 10.1371/journal.pone.0146536
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences in Sequential Decision Making

Abstract: People often make decisions in a social environment. The present work examines social influence on people’s decisions in a sequential decision-making situation. In the first experimental study, we implemented an information cascade paradigm, illustrating that people infer information from decisions of others and use this information to make their own decisions. We followed a cognitive modeling approach to elicit the weight people give to social as compared to private individual information. The proposed social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…Based on the social media posts, it can be inferred that associated with uncertainties about the coronavirus disease and conflicting messages on the internet, the social environment is another factor relevant to the disobedience to protective precautions taken because of its influence on individuals' decision-making processes [35]. The reactions of young people to the basic protective measures taken by the authorities have caused parents to question themselves about the behaviours and attitudes of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the social media posts, it can be inferred that associated with uncertainties about the coronavirus disease and conflicting messages on the internet, the social environment is another factor relevant to the disobedience to protective precautions taken because of its influence on individuals' decision-making processes [35]. The reactions of young people to the basic protective measures taken by the authorities have caused parents to question themselves about the behaviours and attitudes of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the social media posts, it can be inferred that associated with uncertainties about the SARS-CoV-2 infection and con icting messages on the internet, the social environment is another factor relevant to the disobedience to protective precautions taken because of its in uence on individuals' decision-making processes [35]. The reactions of young people to the basic protective measures taken by the authorities have caused parents to question themselves about the behaviours and attitudes of their children.…”
Section: Discussionmentioning
confidence: 99%
“…The literature documents several experimental results on the adoption of behaviors including network structure -such as the study conducted in [5], [7] and decision making [6], [8]. Under these study, it was observed that individual adoption is much more likely when participants received social reinforcement from multiple neighbors in the social network as opposed to a single exposure.…”
Section: Related Work and Conclusionmentioning
confidence: 91%